Conceptual Principles of Decentralization And its Role in the Effective Realization of the Social Function of the State - Ventsel, Viktor (Theory and Practice of Public Administration, 2019)
The development of social and economic processes has necessitated the transformation of a centralized governance model into a decentralized one.From 2014, Ukraine has begun a process of decentralization, the main goal of which is the formation of effective local self-government, which would ensure the creation and maintenance of a full value living environment for citizens, the provision of high-quality and affordable public services. In the process of reform, the leadership of the state and the whole society should rely on the accumulated world experience of decentralization processes.There are several types of decentralization, including political, administrative, fiscal, and economic.Political decentralization envisions giving citizens greater powers when making certain of Nation decisions directly or through means of representative democracy.Administrative decentralization means the redistribution of state functions, powers, responsibilities and financial resources between different levels of authorities. There are three basic forms of administrative decentralization – deconcentration, delegation and devolution.Fiscal decentralization can be implemented in various forms. In particular, this may be: empowering local authorities to introduce taxes and fees, and have a corresponding impact on the administration of tax payments in their territory; provision of targeted or non-targeted transfers from the state budget, municipal borrowings, etc.Economic decentralization is implemented in the form of privatization and deregulation.The main issue is the choice of optimal and efficient combination of different forms of decentralization.At the same time, decentralization conceals numerous risks. For example, standardized monotonous processes can be more effective at the central level due to the scale effect, as well as in cases where there are no qualified specialists at the local level or lack of resources for the local organization of such processes. Sometimes disadvantages of decentralization may be an insufficient correlation of national policy with local priorities. The reservations that could negatively affect decentralization processes should include the risks of increasing uneven distribution of financial resources and increasing disproportions in the social and economic development of the regions.An important aspect in the implementation of decentralization should be the establishment of an optimal balance of functional powers between the central and local levels of government with adequate resource support for the powers of each level of management.For Ukraine today one of the topical issues is the final determination of the type of decentralization model of public administration, an objective assessment of the institutional capacity of the lowest level of management, in which the functions will be performed as effectively and efficiently as possible. The strategic goal of decentralization should be the creation of communities capable of ensuring: the fulfillment of basic social functions; providing the population with the services necessary for life; the formation of basic production and social infrastructure.